Improving management of the larger grain borer, Prostephanus truncatus, and the maize weevil, Sitophilus zeamais - Quellhorst, Hannah E. (Kansas State University, 2023)
The invasive larger grain borer, Prostephanus truncatus (Horn) (Coleoptera: Bostrichidae) is a devastating stored product pest of maize and cassava, originating from Meso-America. Many outstanding areas of basic behavior and ecology remain to be assessed for P. truncatus, and its main cosmopolitan competitor, Sitophilus zeamais (Motschulsky) (Coleoptera: Curculionidae). This includes enhancing knowledge of P. truncatus and S. zeamais management through chemical control, improving understanding of interspecific competition in grain columns, and elucidating how these species potentially vector microbes. To enhance management through chemical control, I investigated the efficacy of a novel insecticide formulation (S-methoprene + deltamethrin + piperonyl butoxide; Gravista®) compared to an existing commercial standard formulation without synergist (Diacon IGR+®), and water-treated controls. We found significant multiple-fold mortality induction and movement reduction when applied as a grain protectant or surface treatment on concrete for 4–168 h compared to the control. In a more realistic test, we evaluated the recovery and horizontal dispersal capacity of P. truncatus and S. zeamais to food patches after 48 h in a dispersal apparatus with 15 g of maize. We found the percentage of P. truncatus and S. zeamais dispersing was significantly reduced by 90–97% or 5–25% after exposure to Gravista or Diacon IGR+ compared to the control. Further, we evaluated two other grain protectants (deltamethrin and pirimiphos-methyl) as surface treatments for maize to manage both species. Mortality of adults was nearly 100% for all treatments for both insecticides with P. truncatus, while progeny production was low. Mortality for S. zeamais remained low for deltamethrin but they were easily controlled by pirimiphos-methyl. These insects also co-occur in many regions of the world. Thus, I evaluated the outcome of interspecific competition between P. truncatus and S. zeamais between 25–35°C and found that coexistence may be possible at a range of 25–30°C, but mixed colonies experienced a direct competitive cost. Prostephanus truncatus than S. zeamais performed better at warmer temperatures. Even less information is available on the spatial dispersion of these species in grain columns, therefore we evaluated competition under three different densities (10–300 insects/kg) in monolayers of maize after 1 and 7 d in pure or mixed colonies. Both species generally aggregated together and were correlated to the same location as heterospecifics. When alone, P. truncatus created a clear path of destruction to the bottom of the monolayer, but when S. zeamais was present, damage was lessened and shifted upwards. Finally, the ability of both species to vector microbes when given the opportunity to forage on agar dishes (e.g., a novel food patch) after a 0, 24, or 72 h dispersal period was assessed. Both species readily vectored several plant pathogenic microbes, including 21 taxa from 11 genera, notably Aspergillus, Penicillium, and Fusarium spp. Increasing dispersal period resulted in a third less microbial growth by S. zeamais after 72 h. Colonization by S. zeamais resulted in 6.6-fold more microbial growth than P. truncatus. This highlights the importance of behavioral ecology in IPM and suggests new tactics for these economically important species.
Keywords: Behavior; Integrated pest management; Microbial ecology; Insect ecology; Stored products; Maize